1999
DOI: 10.1002/(sici)1521-3757(19991115)111:22<3466::aid-ange3466>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Anorganische Materialien mit offenen Gerüsten

Abstract: Neue Materialien mit offenen Gerüsten orientieren sich an ihren natürlichen Vorbildern AUFS¾TZE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
54
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(54 citation statements)
references
References 288 publications
(215 reference statements)
0
54
0
Order By: Relevance
“…[1] A great deal of attention has been paid to the structure-directing role of the organic species, [2] and the structural effect of variously coordinated cations, for example distorted octahedral vanadium [3] and pyramidal tin(ii). [4] Less exploratory work has been carried out on the ªanionicº part of the inorganic network, and most groups reported so far (phosphate, [5] germanate, [6] etc.)…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…[1] A great deal of attention has been paid to the structure-directing role of the organic species, [2] and the structural effect of variously coordinated cations, for example distorted octahedral vanadium [3] and pyramidal tin(ii). [4] Less exploratory work has been carried out on the ªanionicº part of the inorganic network, and most groups reported so far (phosphate, [5] germanate, [6] etc.)…”
mentioning
confidence: 75%
“…Eleven of the twelve symmetryindependent guanidinium hydrogen atoms are involved in Transition metal sulfides (TMSs) are an important class of catalysts that are stable under the severe conditions of sulforeductive hydroprocessing of petroleum-based feedstocks. [1,2] Systematic experimental [2,3] and theoretical [2±5] studies on the hydrodesulfurization (HDS) activity towards dibenzothiophene (DBT) of various metal sulfide catalysts have shown that the strength of the metal ± sulfur bonding plays an important role in the HDS process. Two different models for assessing the MÀS bond strength have been developed.…”
mentioning
confidence: 99%
“…Important materials of this class are for instance the well-known zeolites. [3][4][5][6] Mesopores by definition are found in the range 2 nm < D p < 50 nm. The most prominent member of this class is the so-called MCM-41 introduced in 1992 by Beck, Kresge et al 7,8 The preparation of MCM-41 had already been reported in 1971 by Chiola et al (as delineated in ref.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] In such materials, functionality can be introduced from either the inorganic species or the organic linker molecules. Transition metals are well known to confer redox character to zeolitic hosts, and may impart interesting magnetic and spectroscopic properties to porous materials.…”
mentioning
confidence: 99%
“…Nanochemistry is the synthesis and study of well-defined structures with dimensions of 1 ± 100 nanometers (nm), and thus spans the size range between molecules and materials. [1] While supramolecular chemistry (making small molecules bigger) and microfabrication techniques (making big structures smaller) attack from the flanks, biology employs many constructs of this size. Examples include the photosynthetic reaction center, the ribosome, and membrane-bound receptor-signaling complexes, all notable because of their sophisticated yet modular function.…”
mentioning
confidence: 99%